The factors of consumer behavior when purchasing unit trust fund / Fauziana Mohd Nazmi - Mohd Nazmi, Fauziana (Faculty of Business and Management, 2010)
The purpose of this study is to determine the factors of consumer behavior when purchasing unit trust fund and refine the theoretical framework of the consumers intention to purchase with attitude, self-efficacy, subjective norms, perceived behavioral control, financial literacy and sources of information. A descriptive research design was adopted for this study. From the SPSS analysis, it indicates that there are positive relationships between attitude, self-efficacy, subjective norms, perceived behavioral control, financial literacy, sources of information and intention to purchase unit trust fund. The respondents were working in Unit Trust Fund Management Company, and as such, the socio-economic background of the respondents may not be representative of consumer’s purchase behavior generally. The findings reported in this paper indicate that there is strong relationship between financial literacy and consumer’s intention to purchase unit trust fund where consumers with financial knowledge have higher confidence level when purchasing unit trust. This information should benefit practitioners and researchers alike.